Scalable, anisotropic transparent paper directly from wood for light management in solar cells. (June 2017) - Jia, Chao; Li, Tian; Chen, Chaoji; Dai, Jiaqi; Kierzewski, Iain Michael; Song, Jianwei; Li, Yiju; Yang, Chunpeng; Wang, Chengwei; Hu, Liangbing
Abstract: The growing demand for flexible electronics and solar energy conversion devices has fueled a search for high-quality paper-based materials with excellent mechanical flexibility and optical properties such as high transparency and haze. Despite the tremendous efforts have been dedicated to developing paper-based materials with high transparency or high haze, challenges still remain in achieving both due to the general exclusivity between them. Here, for the first time, we develop a novel anisotropic paper material possessing high mechanical flexibility and fantastic optical properties with both high transmittance ( 90%) and high haze ( 90%) simultaneously via a simple yet effective "top-down" approach by directly shear pressing the delignified wood material. The anisotropic transparent paper demonstrates a high efficiency as a light management coating layer for GaAs solar cell with a significant efficiency enhancement of 14% due to its excellent light management capability with both high transparency and high haze. The presented "top-down" approach is facile, scalable, cost-effective and "green", representing a promising direction for developing flexible electronics, solar energy conversion devices and beyond. Graphical abstract: We demonstrated a highly simple yet efficient "top-down" method for fabricating anisotropic transparent paper by directly shear pressing the delignified wood. The anisotropic paper with both high transmittance of 90% and high haze of 90% can be used as a light management coating layer to significantly improve the energy conversion efficiency of GaAs solar cells. Highlights: A simple yet efficient "top-down" method for fabricating anisotropic transparent paper directly from wood was developed. The wood-derived paper has anisotropic microstructures and light scattering due to the well-aligned cellulose fibers. The anisotropic paper possesses both high transparency and high haze, enabling its utilization in GaAs solar cells. The "top-down" approach for preparing anisotropic transparent paper is facile, scalable, cost-effective and "green".